The role of dental status in the pathogenesis and severity of peritonsillar and cervical infections - Florian Ciprian Venter; Timea Claudia Ghitea; Timea Claudia Ghitea; Adrian Nicolae Venter; Amin-Florin El-Kharoubi; Amin-Florin El-Kharoubi; Mousa El-Kharoubi; Evelin Claudia Ghitea; Marc Cristian Ghitea; Amina Venter (Frontiers in Medicine, 2025)
BackgroundPeritonsillar and cervical infections, such as peritonsillar phlegmon and laterocervical abscesses, are serious complications of oropharyngeal infections. Although poor dental status and inadequate oral hygiene are recognized risk factors, their association with infection severity remains insufficiently explored. This study aimed to assess the relationship between dental status and the clinical severity and management of peritonsillar and cervical infections.Materials and methodsIn this retrospective cohort study, hospitalized patients diagnosed with peritonsillar phlegmon, laterocervical/submandibular abscess, or peritonsillar abscess were included. Clinical and biological data, including dental work, dental implants, dentition quality, treatment, and hospitalization duration, were analyzed. Statistical tests and regression analyses were performed to explore associations between dental status and infection-related outcomes.ResultsPatients with prior dental work or compromised dentition more frequently underwent complex treatments, including corticosteroids. Absence of dental implants was associated with increased antibiotic use and prolonged hospitalization. Although patients with poor dentition required corticosteroids less frequently, they presented more severe infection patterns.ConclusionDental status may be associated with differences in infection severity and treatment patterns among patients with peritonsillar and cervical infections. These findings underscore the potential value of maintaining good oral health as part of a multidisciplinary approach involving ENT specialists and dental professionals.